On-Bottom Stability Analysis of Subsea Pipelines Based on DNVGL RP F109 - Asfarur Ridlwan; Moehamad Syarif Hidayatullah; Elsa Rizkiya Kencana (Department of Naval Architecture - Diponegoro University, 2022)
Subsea pipeline must be design as stable as possible to prevent failure, considering the external forces from current, wave and soil conditions. Based on these problems, the on-bottom stability analysis needs to be considered in the design of the subsea pipeline by referring to the requirements set out in the DNVGL RP F109 2017. The results of the analysis are the value of hydrodynamic force in the horizontal direction which are 99,916 N/m and 204,358 N/m for installation and operating conditions respectively, while the hydrodynamic force in the vertical direction for installation conditions is 46,852 N/m and operating conditions is 192,232. N/m. The result of absolute lateral static stability analysis, the pipe with a concrete coating thickness of 40 mm both in installation and operating conditions is stable, because it has met the criteria. The result of generalized lateral stability analysis, in installation conditions, the displacement of 0,5 and 10 times of pipe diameter have reached the safety factor. Meanwhile, in operating conditions, the displacement of 0,5 times of pipe diameter has not reached the safety factor, while for displacement of 10 times the pipe diameter is alright. Therefore, the concrete ballast thickness needs to be added to become 44 mm. Modeling using ANSYS CFX software was carried out to obtain the value of hydrodynamic forces acting on the pipe. The result of pipe modeling in installation conditions are 83,578 N/m and 57,13 N/m for hydrodynamic forces in the horizontal and vertical directions. The model is verified and categorized as a good numerology and modeling due to the simple data and information as an input in ANSYS CFX.